MicroRNA as a Potential Biomarker and Treatment Strategy for Ischemia-Reperfusion Injury - Mingming Cao; Wenjing Song; Runyu Liang; Lili Teng; Mei Zhang; Jiyao Zhang; Luwen Zhu (International Journal of Genomics)
Ischemia-reperfusion (I/R) injury is a progressive injury that aggravates the pathological state when the organ tissue restores blood supply after a certain period of ischemia, including the myocardial, brain, liver, kidney, and intestinal. With growing evidence that microRNAs (miRNAs) play an important role as posttranscription gene silencing mediators in many I/R injury, in this review, we highlight the microRNAs that are related to I/R injury and their regulatory molecular pathways. In addition, we discussed the potential role of miRNA as a biomarker and its role as a target in I/R injury treatment. Developing miRNAs are not without its challenges, but prudent design combined with existing clinical treatments will result in more effective therapies for I/R injury. This review is aimed at providing new research results obtained in this research field. It is hoped that new research on this topic will not only generate new insights into the pathophysiology of miRNA in I/R injury but also can provide a basis for the clinical application of miRNA in I/R.